2007
DOI: 10.1002/elps.200700299
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous enantioseparation and sensitivity enhancement of basic drugs using large‐volume sample stacking

Abstract: Simultaneous enantioseparation with sensitive detection of four basic drugs, namely methoxamine, metaproterenol, terbutaline and carvedilol, using a 20-mum ID capillary with native beta-CD as the chiral selector was demonstrated by the large-volume sample stacking method. The procedure included conventional sample loading either hydrodynamically or electrokinetically at longer injection times without polarity switching and EOF manipulation. In comparison to conventional injections, depending on the analyte, ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Analysis time decreased from 17 to 14 min for the last peak of myclobutanil enantiomer when the temperature was increased from 25 to 408C. The results obtained in this work agree with those obtained by other authors [20,21], who have found that an increase in temperature causes a reduction in migration time because of the decrease in the viscosity of the buffer solution. However, an increase in the temperature up to 408C reduced the peak area, peak height, and peak efficiencies.…”
Section: Resultssupporting
confidence: 95%
“…Analysis time decreased from 17 to 14 min for the last peak of myclobutanil enantiomer when the temperature was increased from 25 to 408C. The results obtained in this work agree with those obtained by other authors [20,21], who have found that an increase in temperature causes a reduction in migration time because of the decrease in the viscosity of the buffer solution. However, an increase in the temperature up to 408C reduced the peak area, peak height, and peak efficiencies.…”
Section: Resultssupporting
confidence: 95%
“…Furthermore, on-column preconcentration can also be attained by electrokinetic injection (for assay examples see Refs. [51,54,57,73,75,89,103,108,116,145]) and stacking procedures [49,71,75,79,87,100,108,116]. Electrophoretic mass transport is highly regulated, this allowing charged solutes to be concentrated (stacked) across an electrolyte discontinuity, including that produced initially between sample and running buffer.…”
Section: Principlesmentioning
confidence: 99%
“…Denola et al [77] reported the application of LVSS for sensitivity enhancement for the enantiomeric separation of four basic drugs (methoxamine, metaproterenol, terbutaline, and carvedilol) using b-CD as the chiral selector. Several 100-to 1000-fold enhancements in sensitivity were achieved with hydrodynamic and electrokinetic injections, respectively.…”
Section: Fessmentioning
confidence: 99%